When Social Media Influencers Go Political: An Exploratory Analysis on the Emergence of Political Topics Among Finnish Influencers. Issue 3 (3rd July 2022) - Suuronen, Aleksi; Reinikainen, Hanna; Borchers, Nils S.; Strandberg, Kim
Abstract : Social media influencers are often understood as non-political actors who, due to the impact they exert on their followers' purchase decisions and brand attitudes, play an important role in marketing and branding. In recent years, various influencers have addressed political issues during important political events such as elections. This political aspect of social media influencing has not received much scholarly interest thus far. In one of the first exploratory studies on the topic, we surveyed over one hundred Finnish influencers and investigated the degree to which they engaged with political topics. Our results show that political topics are commonly brought up among Finnish influencers. However, many influencers also deliberately avoid addressing them because they fear what comments and conversations these topics could generate and that they could personally be targeted by aggressive internet commentators. Nevertheless, based on our findings, we argue that the digital spaces maintained by influencers can constitute a new kind of third space where the emergence of political topics can have a greater impact on the political behaviour of influencers' followers.